KAJIAN STATUS WADUK TIRTA SHINTA DAN KELAYAKANNYA UNTUK INDUSTRI ETHANOL DI KOTABUMI LAMPUNG UTARA - Agung Riyadi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
PT. Medco Ethanol Lampung has been constructed factory for cassavaand mollase processing in order to product Rectified-Ethanol at Talang JaliVillage, Kotabumi North Lampung. The estimation of capacity productionis around 190.000 liter per day. Maximum necessity of fresh water forfactory operasional is about 8.507 m /hari. For the measurement depthand water volume Tirta Shinta Reservoir get the volume is about3.155.434 m with the avarage depth for 1 – 6 meter, while the dischargeof water at outflow for agricultural is about 138.270 m per day at rainyseason. If the water from Tirta Shinta reservoir use for main factory, andthe total capacity reservoir only used 4.3 %, if nothing flow from riverbecause dry season, and now Tirta Shinta reservoir can be supply only17.7 month during dry season. Based on the environmental aspect, ifbetter, a fresh water supply for ethanol factory from river has a big rate offlow. This present, beside for farming activity and tourism, the most ofsurface water reservoir covered by water plant that make problem forfactory operational, specially for water pump.